ASD closure under pressure. (11th September 2014) - Shebani, Suhair Omar; Skinner, Gregory James; Duke, Christopher
Abstract : Transcatheter atrial septal defect device implantation in elderly patients may cause acute pulmonary oedema when impaired left ventricular diastolic function causes an abrupt increase in left atrial pressure. Though left atrial pressure is often monitored during test occlusion of a defect, it is not clear at what cut-off value device implantation is contraindicated. We report successful closure of an atrial septal defect in a 73-year-old patient, even though the mean left atrial pressure increased from 18 to 25 mm Hg with device implantation. Although a fenestrated device was used, this did not prevent the rise in left atrial pressure. The patient was supported with mechanical ventilation, milrinone and intravenous diuretics following the procedure and did not develop pulmonary oedema. Her dyspnoea improved and her functional status increased from New York Heart Association (NYHA) III to NYHA II. In conclusion, successful device closure can be accomplished even with high left atrial pressure.